Oral bisphosphonate therapy for vitamin D intoxication of the infant - BEREKET, ABDULLAH; GÜRAN, TÜLAY (AMER ACAD PEDIATRICS, 2003)
Vitamin D intoxication in infancy has serious consequences attributable to acute hypercalcemia and subsequent hypercalcuria/nephrocalcinosis. Current treatments of patients with vitamin D intoxication are unsatisfactory and associated with prolonged hypercalcemia. We now report the use of oral alendronate sodium in a 3-month-old infant with vitamin D intoxication. Short-term oral alendronate sodium treatment effectively corrected hypercalcemia/hypercalciuria, decreased the duration of hospitalization, and appears safe in 15 months of observation.
Keywords: bisphosphonates; hypercalcemia; hypervitaminosis D; HYPERCALCEMIA; PAMIDRONATE; CHILDREN